AVALIAÇÃO DA CONCENTRAÇÃO DE LEPTINA SALIVAR E SUA CORRELAÇÃO COM PARÂMETROS SÉRICOS E PERIODONTAIS EM PACIENTES COM LÚPUS ERITEMATOSO SISTÊMICO. - SILVA, LESLIE ALVES DA (2018)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease, of unknown etiology, with a great destructive power, that may involve isolated or multiple organs, due to the body's immune hyperactivity. Leptin is a proinflammatory cytokine, produced mainly by the adipose tissue, of great importance in the perpetuation of chronic inflammation of autoimmune diseases, since it stimulates the production of proinflammatory cytokines such as Interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α), which in turn increase leptin synthesis. In chapter I, a cross-sectional study in which 67 patients were selected, being 38 patients with LES and 29 systemically healthy patients. The aim of this study was to investigate the salivary levels of leptin and correlate them with serum and periodontal parameters of patients with SLE. Saliva was collected by the total stimulated saliva method and salivary leptin concentration analysis was performed using Luminex MAGPIX®. Student's t-test was used in the comparative analysis of leptin salivary concentration between SLE patients and systemically healthy individuals. The Spearman coefficient (Rs) was calculated to estimate the correlation between salivary leptin and serum and periodontal parameters. In the theoretical model proposed for the study of leptin salivary changes due to SLE, periodontal disease was tested as a mediator variable. The model was tested using Structural Equation Modeling. The level of significance was 5%. It was found that patients with SLE had statistically lower levels of salivary leptin than systemically healthy patients (P = 0.002) and that the reduction of the level of salivary leptin in SLE patients overlaps with the presence of periodontal disease. 0.298, P = 0.023). The data showed that salivary leptin concentration correlated with triglycerides (Rs -0.534, P = 0.003), creatinine (Rs -0.331, P = 0.048), creatinine clearance (Rs -0.445, P = 0.025), leukocytes -0.331, P = 0.041) and cholesterol (Rs 0.434, P = 0.016) and showed no correlation with periodontal parameters (P> 0.05). These results point to leptin as a promising salivary marker, low cost and easy to obtain in patients with SLE, besides the possibility of being able to correlate its levels with important serum parameters of patients with the autoimmune disease.